Effects of growth temperature on the photovoltaic properties of RF sputtered undoped NiO thin films - Jamal M.S.; Shahahmadi S.A.; Chelvanathan P.; Alharbi H.F.; Karim M.R.; Ahmad Dar M.; Luqman M.; Alharthi N.H.; Al-Harthi Y.S.; Aminuzzaman M.; Asim N.; Sopian K.; et al. (Elsevier B.V., 2023)
In this study, nickel oxide (NiO) thin films were deposited on soda lime glass using radio-frequency magnetron sputtering at different growth (substrate) temperatures ranging from room temperature (RT) to 400 C. The effects of substrate temperature on the structural, morphological, electrical, and optical properties were investigated. The XRD pattern unveiled a dominant peak with (2 0 0) preferential orientations for the film grown at 100 C. However, for samples grown at high temperatures, a gradual decrease of (2 0 0) peak intensity was observed, which may be the result of the decomposition of NiO as confirmed via EDX. Surface morphology from FESEM revealed that grains were randomly orientated on the surface with maximum grain size of 19.43 nm. Upon increasing the growth temperature, the crystal quality and grain size substantially deteriorated, which is consistent with the XRD results. Scanning probe microscopy (SPM) finds rough surface with the highest surface roughness obtained at RT with a value of 1.232 nm. Electrical resistivity was found to be highly dependent on the growth temperature that decreases from 2150 ? cm to 72 ? cm as the substrate temperature increases. For optical properties, the optical bandgap of the NiO films decreases from 3.8 eV to 3.2 eV as a function of substrate temperature as derived from the optical transmittance data. Results show the potential application of the NiO films in photovoltaic devices. 2019 The Authors